Implementasi Permainan Tradisional Bola Bekel sebagai Media Pembelajaran Interaktif Gaya Gravitasi - Diyah Andini Kusumastuti; Umi Mahmudah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The era of digitalization has a significant impact on various aspects of life, including education. However, the existence of traditional games is increasingly eliminated due to technological developments. This study examines the implementation of the traditional game of ball ball as an interactive learning medium of the earth's gravitational force for elementary / middle school students. Using the Systematic Literature Review (SLR) method, this study identifies the benefits of the game of ball ball in improving students' understanding, motivation, and learning outcomes through a fun and interactive approach. The results of the study show that the ball game is able to integrate the concept of the earth's gravitational force in a simple but effective way. The game also facilitates the development of students' cognitive, psychomotor, affective, social, and spiritual aspects. The use of the game of ball in learning not only increases students' interest but also creates an inclusive and collaborative learning environment. The conclusion of this study confirms that the traditional game of bekel ball is an innovative and relevant learning medium in teaching physics concepts, especially the earth's gravitational force. The practical implications can be used as a guideline for educators to develop learning strategies based on local wisdom that support in-depth conceptual understanding. Further research is recommended to explore the potential of other traditional games in the learning of complex science concepts.